Utilising advance care planning videos to empower perioperative cancer patients and families: a study protocol of a randomised controlled trial. Issue 5 (6th June 2017) - Aslakson, Rebecca A; Isenberg, Sarina R; Crossnohere, Norah L; Conca-Cheng, Alison M; Yang, Ting; Weiss, Matthew; Volandes, Angelo E; Bridges, John F P; Roter, Debra L
Abstract : Introduction: Despite positive health outcomes associated with advance care planning (ACP), little research has investigated the impact of ACP in surgical populations. Our goal is to evaluate how an ACP intervention video impacts the patient centredness and ACP of the patient-surgeon conversation during the presurgical consent visit. We hypothesise that patients who view the intervention will engage in a more patient-centred communication with their surgeons compared with patients who view a control video. Methods and analysis: Randomised controlled superiority trial of an ACP video with two study arms (intervention ACP video and control video) and four visits (baseline, presurgical consent, postoperative 1 week and postoperative 1 month). Surgeons, patients, principal investigator and analysts are blinded to the randomisation assignment. Setting: Single, academic, inner city and tertiary care hospital. Data collection began July 16, 2015 and continues to March 2017. Participants: Patients recruited from nine surgical oncology clinics who are undergoing major cancer surgery. Interventions: In the intervention arm, patients view a patient preparedness video developed through extensive engagement with patients, surgeons and other stakeholders. Patients randomised to the control arm viewed an informational video about the hospital surgical programme. Main outcomes and measures: Primary Outcome: Patient centredness and ACP of patient-surgeon conversations during the presurgical consent visit as measured through the Roter Interaction Analysis System. Secondary outcomes: patient Hospital Anxiety and Depression Scale score; patient goals of care; patient, companion and surgeon satisfaction; video helpfulness; medical decision maker designation; and the frequency patients watch the video. Intent-to-treat analysis will be used to assess the impact of video assignment on outcomes. Sensitivity analyses will assess whether there are differential effects contingent on patient or surgeon characteristics. Ethics and dissemination: This study has been approved by the Johns Hopkins School of Medicine institutional review board and is registered on clinicaltrials.gov (NCT02489799, First received: July 1, 2015). Trial registration number: clinicaltrials.gov, NCT02489799 .